A comparison of market entry strategies adopted by Information and Communication Technology (ICT) firms from major and emerging software exporting nations. (21st October 2009) - Kelly, Stephen; Harrison, Jennifer
This study examines the market entry practices of Australian and Pakistani Information and Communication Technology (ICT) firms and the proposition that Local Software Economy (LSE) maturity affects the selection of market entry practices. The question is significant as it is focused on an indirect effect – namely LSE maturity – on the adoption of market entry practices, with indirect effects being identified in recent literature as being significant and an area in need of further research. The findings provide support for the proposition, indicating that Australian and Pakistani firms, representative of firms operating in high and low maturity LSEs, respectively, adopt a range of different practices relating to international engagement, geographic focus, market entry strategies and international market offering.